The Effects of Hand and Foot Massage Based on Comfort Theory on the Decrease in Fatigue and Anxiety Values in Chronic Kidney Failure Patients Undergoing Hemodylalysis - Anastasia Mampesi; Umdatus Soleha; R. Khairiyatul Afiyah; Siti Nur Hasina (Indonesian Journal of Global Health Research, 2026)
Complaints that often arise in hemodialysis patients are nausea, vomiting, anemia, fatigue, sleep disorders, and increased urea levels. Anxiety is caused by by innate and physiological factors, namely those that influence or manifest in physical symptoms, especially in the function of the central nervous system, both from within the patient and from outside the patient. This study aims to provide scientific evidence to support the use of these interventions as a comfortable and effective prevention strategy for patients with chronic kidney failure. Comforting intervention needed in nursing intervention, the comfort level of Kolkaba is at the transcendence comfort level. The method used is quasy experimental with a pretest-posttest control group design approach, the sample size is 40 people, namely 20 interventions groups and 20 controls groups. The sampling technique is Purposive Sampling Technique. The research instrument used the Fatigue Severity Scale (FSS) questionnaire and DASS 42. FSS shows high reliability with Cronbach's Alpha value >0.9, such as 0.968 as well as good validity based on Pearson correlation (r >0.623, Sig <0.05). The DASS-42 has excellent reliability (Cronbach's Alpha >0.9 for each dimension: depression 0.954, anxiety 0.903, stress 0.917) and validity 0.782. The data were analyzed using the Pariet t- test with significance at fatigue p = 0.000 (<0.05). While anxiety shows the Pariet t- test with significance p = 0.015 (<0.05), indicating that hand and foot massage therapy has an effect on reducing fatigue and anxiety values. The conclusion of this study is that there is an effect of hand and foot massage based on the theory of comfort on reducing fatigue and anxiety values in chronic kidney failure patients undergoing hemodialysis.